Miner Bee, Chimney Bee Anthophora abrupta Say - Jason R. Graham; Jamie Ellis; Glenn Hall; Catherine Zettel Nalen (EDIS)
These gregarious, yet solitary, ground-nesting bees are “…conspicuous as they noisily swing their ponderous bodies to and fro on the wing, arrive home and scramble into their burrows or come tumbling out headlong and dash off into the sunny fields, with all the exuberance of boys just out of school.” This 5-page fact sheet was written by Jason R. Graham, Jamie Ellis, Glenn Hall, and Catherine Zettel Nalen, and published by the UF Department of Entomology and Nematology, December 2011.